Estudo de ligas de níquel produzidas In-situ pela deposição simultânea das ligas Inconel 625 e Hastelloy C276 por soldagem MIG/MAG com duplo arame - Barreto, Alexandre Sousa (2018)
The application of nickel based superalloys in oil and gas industry equipment has increased development. The use of the GMAW process with two wires configuration to manufacture components for this industrial sector, allows mainly combine different filler metals in the weld pool. The aim of this study is to evaluate the impact of the degree of mixing between the alloys on various aspects, including the microstructure, mechanical properties and corrosion resistance. The welds were performed by the Tandem GMAW process with the longitudinal position of the electrodes using pure argon as shielding gas. The methodology consists in the welding of coatings with three mixing ratios, 50% 50% (Alloy A) 65% 35% (Alloy B) 35% 65% ( Alloy C) of C276 and 625 alloys, respectively, on ASTM steel plates A516 Gr 60 with a thickness of 40mm. After welding was performed metallurgical characterization of the alloy using scanning electron microscope (SEM), instrumented Charpy impact tests and Vickers hardness to determine mechanical properties, and the corrosion test according to ASTM G48 - Method C. The resulting microstructure of weldes coatings were composed of a γ matrix with columnar and cellular dendrite growth predominantly. Regions were observed at the bottom of the weld beads with the highest concentration of Hastelloy C276 in all coatings. The toughness was not significantly influenced by the composition of alloy. The level of hardness for the welded coatings was around 265 HV0.1. The corrosion resistance test showed that the alloy with highest Hastelloy C276 content reached a temperature of 85 °C, since the condition C had a critical temperature pitting of 80oC. The Alloy A (50% C276 50% 625) was considered the better for the study because it is composed of equal proportions of alloys and achieved satisfactory results for the microstructure analysis, impact energy and hardness and corrosion resistance having this shape, similar behavior to the top leagues of higher cost.